1967
DOI: 10.1246/bcsj.40.2731
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects in the Electron Spin Resonance Spectra of Some Phenoxyl, Nitroxide, and Anilino Radicals

Abstract: The electron spin resonance spectra of 2, 6-di-t-butyl-4-methylphenoxyl (I) and 2, 4, 6-tri-t butylphenoxyl (II) have been observed under high resolution, and it has been shown experimentally that the para methyl proton hyperfine splitting (a&) in the radical (I) increases, while, inversely, the meta proton hyperfine interaction decreases, as the dipole moment of the solvent (u) increases. The relationship between these two variables can be written as:where ,ueot, is the dipole moment of the solvent and where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Then, the ESR spectra were obtained in the presence of TTBP and 2,6-DTBO ( Figure 8 c,d). The observed spectra were assigned to their corresponding phenoxyl radicals (PhO • ) [ 29 , 30 ]. The hfccs were simulated from the measured spectra, which confirm the generation of a PhO • through the PCET involving one or two PTs and one ET between the compounds and O 2 •− .…”
Section: Resultsmentioning
confidence: 99%
“…Then, the ESR spectra were obtained in the presence of TTBP and 2,6-DTBO ( Figure 8 c,d). The observed spectra were assigned to their corresponding phenoxyl radicals (PhO • ) [ 29 , 30 ]. The hfccs were simulated from the measured spectra, which confirm the generation of a PhO • through the PCET involving one or two PTs and one ET between the compounds and O 2 •− .…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that A 0 for a nitroxide spin probe such as 5DSE varies systematically with the solvent polarity, [11][12][13] so the previous work 9,10 showed that as the micelle grew because of increasing [SDS], the polarity sensed by 5DSE decreased.…”
Section: Combining Eqs 1 and 2 Yieldsmentioning
confidence: 99%
“…The spectrum for TI was broad probably due to the aggregation (association) of TI in the St medium, and that for BHT clearly split into four peaks (1:3:3:1 ratio: hypersplitting constant a H = 11.20 G) by the methyl group at the para position and further split into three peaks (1:2:1 ratio: a H = 1.67 G) by the protons at the meta positions. 17 The spectrum for CHD was somewhat noisy due to the lower concentration of A • than those for TI and BHT. The spectrum split into three peaks (1:2:1 ratio: a H = 42 G) because of the protons at the meta positions and further split into two peaks (1: 1 ratio: a H = 18 G) because of the proton at the central position.…”
Section: Introductionmentioning
confidence: 99%